CHARACTERISTICS AND STRUCTURES OF STORYTELLING TECHNIQUES IN CRIMINAL, HORROR, AND MYSTERY GENRES OF YOUTUBERS STORYTELLERS - Glenity Marchella Siauw; Lambok Hermanto Sihombing (Metacommunication: Journal of Communication Studies, 2022)
YouTube is  the biggest  platform of  sharing and  watching online videos that enable everyone to have their own channel and upload their own contents. As YouTube attracts people’s interest, this research explores the characteristics and structure of storytelling techniques on storyteller YouTuber. This research analyzes how the storyteller  YouTubers  use  storytelling  techniques  to  deliver  the story and how are the audience’s opinion towards the storytelling techniques of the YouTubers, focusing on three big YouTube channels, which is Nessie Judge. This research discovers the unique characteristics of each YouTuber that differentiate them one another. As the data, researcher chooses three videos of each YouTuber between January 2021  to  November  2021  to  analyze  the  storytelling  techniques, audiences’  reception  through  the  comment  section  and  used sounds or music in the video. To answer the research questions, researcher applied three theories, which are Storytelling Theory, Audience Reception Theory and Sound Theory.   The result of the research shows that these three YouTubers have their own unique characteristic   that   attracts   the   audiences’   attention   to   keep watching their contents.